Voir, Faire voir et apprendre à voir - Vanessa Rémery; Nelly Duret Benou (Revue d'anthropologie des connaissances)
This paper proposes a study of vocational and training activities in a particular medical and technological environment, fetal ultrasound. It presents some findings from an exploratory research realized in collaboration with the Fetal Medicine and Ultrasound Unit of an hospital. The aim of the study is to examine how ultrasound practitioners, physicians and midwives, work. We highlight the practical, tacit and embodied knowledge mobilized for the production and interpretation of fetal ultrasound images. Based on a video-ethnographic study of the practical accomplishment of work and training, we analyze the skills of sonographers to highlight their visual abilities. Specifically, we focus on how to see, how to show, and how to learn to see the images produced in order to make a diagnosis and communicate it to the patients. We propose to describe these various registers of seeing, as they constitute a central dimension of the sonographers’ professional vision, and to highlight the instrumental mediations involved in the production and interpretation process of images.